Stabilities of Alkaline Earth Metal Ion Complexes with Dicyclohexano-18-Crown-6 in Acetonitrile-Water Binary Solutions - ROUNAGHI, G.H.; RAHIMI BAJESTANI, M.; GHAEMI, A. (Asian Journal of Chemistry, 2010)
Conductivities of alkaline earth metal salts in the presence of dicyclohexano-18-crown-6 (DCH18C6) were measured at different temperatures in acetonitrile-water (AN-H2O) binary solutions. The stoichiometry of the complexes in most cases was found to be 1:1 (ML2+), but in the case of complexation of Ca2+ and Ba2+ cations with DCH18C6 in pure acetonitrile, 1:2 (ML22+) complexes are formed in solutions. Formation constants of 1:1 complexes (ML2+) of DCH18C6 with Mg2+, Ca2+, Sr2+ and Ba2+ metal cations were determined using conductometric data. The results show that the stabilities and selectivities on complexation processes are governed by the solvent medium and the relative size of the metal cations and DCH18C6 cavity. An anomalous and interesting behaviour was observed for the case of complexation of Ca2+ and Ba2+ metal cations with the ligand in pure acetonitrile. In all cases, a non-linear behaviour was observed for variation of log Kf of the metal ion complexes vs. the composition of the acetonitrile-water binary solution. It was found that the selectivity order of DCH18C6 for the metal cations is changed in some composition of the mixed solvent. The values of thermodynamic quantities (ΔHºc and ΔSºc) for formation of complexes were obtained from temperature dependence of the formation constants of complexes using the van't Hoff plots. With the exception of complexation of Ca2+ ion with DCH18C6, the complexation reactions are enthalpy destabilized but entropy stabilized and the values of the thermodynamic parameters are influenced by the nature and composition of the mixed solvents.